1974
DOI: 10.1029/ja079i004p00665
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of the ionosphericFregion during the Great Solar Flare of August 7, 1972

Abstract: The response of the ionospheric F region to the large solar flare that occurred near 1500 UT on August 7, 1972, has been monitored by means of Faraday rotation measurements made at 17 stations in North America, Europe, and Africa. With observations spanning more than 10 hours in local time and more than 70 deg in latitude, the first truly global morphology of a flare‐induced F region event was obtained. The sizes of the individual sudden increases in the total electron content (Sitec) ranged from 1.8 to 8.6 × … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(79 citation statements)
references
References 12 publications
(1 reference statement)
3
72
4
Order By: Relevance
“…The estimate obtained is consistent with the findings reported by Mendillo and Evans (1974a); Mendillo et al (1974b). The authors of the cited references, based on investigating the electron density profile in the height range from 125 km to 1200 km using the IS method, concluded that about 40% of the TEC increase during the powerful flare on 7 August 1972 corresponds to ionospheric regions lying above 300 km.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The estimate obtained is consistent with the findings reported by Mendillo and Evans (1974a); Mendillo et al (1974b). The authors of the cited references, based on investigating the electron density profile in the height range from 125 km to 1200 km using the IS method, concluded that about 40% of the TEC increase during the powerful flare on 7 August 1972 corresponds to ionospheric regions lying above 300 km.…”
Section: Resultssupporting
confidence: 88%
“…On 7 August 1972, Mendillo et al (1974b) were the first to make an attempt to carry out global observations of the solar flare using 17 stations in North America, Europe, and Africa. The observations covered an area, the boundaries of which were separated by 70 • in latitude and by 10 h in local time.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies of terrestrial effects of solar flares have focused on the ionospheric aspects (e.g., Mitra 1974; Davies 1990;Mendillo et al 1974;Zhang et al 2005;Tsurutani et al 2006), with relatively sparse research concerning the thermosphere (Sutton et al 2005;Liu et al 2007a;Pawlowski and Ridley 2008). The thermosphere, with its large mass and high heat capacity, is expected to be slower in responding to transient events such as solar flares.…”
Section: Response To Solar Flaresmentioning
confidence: 99%
“…These rapid increases directly enhance ionization in the upper atmosphere, causing "sudden ionospheric disturbances" (SID), which disrupts navigation systems and communications that rely on ionosphere electron density. Consequently, many phenomena associated with SID, including short wave fadeout, sudden phase anomalies, and (magnetic) solar flare effects, have been investigated since the 1950s [e.g., Shain and Mitra, 1954;Mendillo et al, 1974;Davies, 1990;Manju and Viswanathan, 2005]. Most ionosphere responses to solar flares have been attributed to, and can be explained by, the enhancement of solar X-rays and EUV during solar flares.…”
Section: Introductionmentioning
confidence: 99%